Evaluating physicians’ awareness and prescribing trends regarding proton pump inhibitors: a cross-sectional study - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Ibrahim, Ahmed R. N.; Siddiq, Abdelmonem; Jawish, Nagham; Makhoul, Mark Hasib; Alrezej, Maram Abdulmajid Mahmoud; Makhoul, Fouad Hasib; Sawaf, Bisher; Hafez, Wael; Makram Elsayed, Sarah; et al. (Frontiers in Pharmacology, 2023)
Introduction: Proton pump inhibitors (PPIs) are commonly used to treat acid-related disorders. Their appropriate use depends on the correct indications from the clinician. Owing to the high incidence of use and misuse, PPIs have been identified as an essential pharmacological class for developing deprescribing recommendations. Therefore, assessing physicians’ knowledge and practice regarding PPI usage is critical for paving the way toward targeted recommendations and efforts. Objective: This study aimed to assess Syrian physicians’ perceptions of proton pump inhibitors adverse effects, their benefit in upper gastrointestinal bleeding (UGIB) prophylaxis, and how these perceptions are related to PPI prescription practice. Methods: A cross-sectional study was performed using a web-based questionnaire distributed among Syrian physicians in internal medicine between 28 November and 23 December 2022. The questionnaire assessed perceptions and experiences of PPIs, concerns about specific adverse effects, and their effectiveness for UGIB prophylaxis, in addition to the different scenarios used to determine the best practice for appropriate treatment to manage minimal, mild, moderate, and high-risk UGIB patients. Results: A total of 473 participants completed the questionnaire, with median age ±SD was (28.46 ± 4.58), and most participants (83.3%) were residents. Approximately half of the participants (45.5%) agreed that discussion assistance was provided to continue or terminate PPIs properly. Only 8.9% were very familiar with published evidence of PPI adverse effects. Bone weakening and vitamin B12 deficiency were the most frequently reported side effects (81.8% and 79.7%, respectively). However, dementia (0.4%) and mortality (1.9%) were the least reported adverse effects. More than half of the participants (64%) perceived using PPIs to prevent upper GI bleeding. Non-trainee physicians were less knowledgeable about appropriate GERD management than resident physicians (p < 0.001). Conclusion: The study showed a gap between Syrian physicians’ perceptions and practices regarding PPI use, which necessitates spreading awareness of updated guidelines for PPI usage and their side effects.